A multi‐institutional analysis of peritransplantation radiotherapy in patients with relapsed/refractory Hodgkin lymphoma undergoing autologous stem cell transplantation. Issue 8 (16th December 2016) - Milgrom, Sarah A.; Jauhari, Shekeab; Plastaras, John P.; Nieto, Yago; Dabaja, Bouthaina S.; Pinnix, Chelsea C.; Smith, Grace L.; Allen, Pamela K.; Lukens, J. Nicholas; Maity, Amit; Oki, Yasuhiro; Fanale, Michelle A.; et al.
Abstract : BACKGROUND: No consensus exists regarding the use of radiotherapy (RT) in conjunction with high‐dose chemotherapy and autologous stem cell transplantation (HDC/ASCT) for patients with relapsed/refractory classical Hodgkin lymphoma (HL). The objectives of the current study were to characterize practice patterns and assess the efficacy and toxicity of RT at 2 major transplantation centers. METHODS: Eligible patients underwent HDC/ASCT from 2006 through 2015 using the combination of either carmustine (BCNU), etoposide, cytarabine, and melphalan (BEAM) or cyclophosphamide, BCNU, and etoposide (CBV). RESULTS: For the cohort of 189 patients, the 4‐year overall survival rate was 80%, the progression‐free survival rate was 67%, and the local control (LC) rate was 68%. RT was used within 4 months of ASCT for 22 patients (12%) and was given more often for disease that was early stage, primary refractory, or [ 18 F]fluorodeoxyglucose (FDG)‐avid at the time of HDC/ASCT. Disease recurrence occurring after HDC/ASCT was associated with primary refractory disease and FDG‐avidity at the time of HDC/ASCT. RT was not found to be associated with LC, progression‐free survival, or overall survival on univariate analysis. In a model incorporating primary refractory HL and FDG‐avid disease at the time of HDC/ASCT, RT was found to be associated with a decreased risk of local disease recurrence (hazard ratio, 0.3; P = .02). In patients with primary refractory HL and/or FDG‐avid disease at the time of HDC/ASCT, the 4‐year LC rate was 81% with RT versus 49% without RT ( P = .03). There was one case of Common Terminology Criteria for Adverse Events grade ≥ 3 RT‐related toxicity (acute grade 3 pancytopenia). CONCLUSIONS: In patients undergoing ASCT for relapsed/refractory HL, peritransplantation RT was used more often for disease that was early stage, primary refractory, or FDG‐avid after salvage conventional‐dose chemotherapy. RT was associated with improved LC of high‐risk localized disease and was well tolerated with modern techniques. Cancer 2017;123:1363–1371. © 2016 American Cancer Society . Abstract : In a multi‐institutional cohort of patients who underwent autologous stem cell transplantation for relapsed/refractory Hodgkin lymphoma, peritransplantation radiotherapy was used more often for disease that was early stage, primary refractory, or [ 18 F]fluorodeoxyglucose‐avid after salvage conventional‐dose chemotherapy. Radiotherapy was associated with improved local control of high‐risk localized disease and was well tolerated with modern techniques.